2013
DOI: 10.1007/s00894-013-1946-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms on electrical breakdown strength increment of polyethylene by acetophenone and its analogues addition: a theoretical study

Abstract: A theoretical investigation is completed on the mechanism of electrical breakdown strength increment of polyethylene. It is shown that it is one of the most important factors for increasing electrical breakdown strength of polyethylene through keto-enol isomerization of acetophenone and its analogues at the ground state S0 and the lowest triplet state T1. The minimum structures and transition states of the keto- and the enol-tautomer of acetophenone and its analogues at the S0 and T1 states are obtained at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Herein, we aim to investigate the possibility of the radical formation of Vp and Bp compared with Pe during the process of producing UV radiation cross-linking polyethylene insulation materials for high voltage cables. The calculated DE T1-S0 (the relative energy margins between the S 0 and T 1 states) at the QCISD(T)//B3LYP level of acetophenone was 74.92 kcal mol À1 in our previous study, 17 which is consistent with the reported experimental value of 73.74 kcal mol À1 . 25 The calculated DE T1-S0 at the QCISD(T)/6-311+G(3df,2p)//B3LYP/6-311+G(d,p) level of benzophenone is 2.95 eV in this study, which is in good agreement with the experimental value of 24 224 cm À1 (3.00 eV) reported by Ito and co-workers.…”
Section: Energetics and Mechanismsupporting
confidence: 90%
See 1 more Smart Citation
“…Herein, we aim to investigate the possibility of the radical formation of Vp and Bp compared with Pe during the process of producing UV radiation cross-linking polyethylene insulation materials for high voltage cables. The calculated DE T1-S0 (the relative energy margins between the S 0 and T 1 states) at the QCISD(T)//B3LYP level of acetophenone was 74.92 kcal mol À1 in our previous study, 17 which is consistent with the reported experimental value of 73.74 kcal mol À1 . 25 The calculated DE T1-S0 at the QCISD(T)/6-311+G(3df,2p)//B3LYP/6-311+G(d,p) level of benzophenone is 2.95 eV in this study, which is in good agreement with the experimental value of 24 224 cm À1 (3.00 eV) reported by Ito and co-workers.…”
Section: Energetics and Mechanismsupporting
confidence: 90%
“…[9][10][11][12][13][14][15] Using theoretical studies, our group rst elucidated the mechanisms of aromatic carbonyl compounds as voltage stabilizers for increasing the electrical breakdown strength of XLPE in 2013. [16][17][18] Acetophenone is an example of an aromatic carbonyl compound that can function as a voltage stabilizer; however, it easily migrates out of the polymeric matrix. Thus, aromatic carbonyl and benzil-type compounds with a larger alkoxy chain can effectively increase the compatibility with the polyethylene matrix and improve the electrical treeing inception level signicantly.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the acetphonene was demonstrated that keto‐enol tautomerism reactions focus on S 0 and T 1 . In previous works of our group, the tautomerism reaction potential barriers at S 0 and T 1 of acetophonene are 62.31 kcal/mol (2.7 eV) and 28.71 kcal/mol (1.24 eV), respectively, which are much smaller than the average CC bond energy(82.95 kcal/mol = 3.59 eV) of polyethylene . The discussion above indicates acetophoene can undergo isomerization reaction, absorbing and consuming the energies of “hot electrons.” As a result, it can play an important role on inhibiting the electric breakdown.…”
Section: Resultsmentioning
confidence: 90%
“…So called “hot electrons” are formed during the process of charges transportation and accumulation as high voltage was stressed on the insulated cables for long time, and there is much energy released. The “hot electrons” could further excite the defect parts from ground state to excited state (the excited energy 6.01 eV of C 8 H 16 O calculated by TDDFT is given in Table ), or break CC bond of polyethylene (3.59 eV CC breaking energy). Obviously, CC breaking is easier and result in electric treeing initiated in the end.…”
Section: Resultsmentioning
confidence: 99%
“…Jarvid’s studies have shown that fullerenes are very efficient voltage stabilizers and can find potential applications in power cables. Most voltage stabilizers have an aromatic or benzophenone-like structure, such as acetophenone (AP) [19,24] or benzyls [25], which can effectively inhibit the formation of electrical tree; however, these voltage stabilizers have poor compatibility with XLPE, which causes them to migrate out of XLPE, influencing the lifetime and properties of the insulation material. The issue of voltage stabilizer migration has recently attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%